SYSTEMATIC LITERATURE REVIEW ON 3D PRINTING PERSONALISED FOOD FOR THE ELDERLY - Haris, Muhammad Salahuddin; Kamarudin, Nur Fatin Adlin; Mohamed Aini, Khairul Auni Adli; Abdul Rais, Harith Juwaidi; Mohd Rus, Shaiqah; Harith, Sakinah (Malaysian Journal of Science, 2022)
Three-dimensional (3D) printing is currently a new technology being developed in the food industry due to its ability to design, customize, and fabricate a product with good precision and accuracy. Therefore, with regard to the mastication problems frequently faced by elderly people, this technology is utilized to design foods that can be consumed by them. Since there was limited published literature on the subject, the present study aimed to systematically review 3D printing personalized food for the elderly. The study used PRISMA as a guideline for report writing while integrating multiple research designs. This paper employed three databases to select the articles: Science Direct, Scopus, and Google Scholar. The study included five analyzed themes: 1) hardness; 2) moisture; 3) viscosity; 4) elasticity; and 5) printability. The study significantly contributed to several practical purposes and the body of knowledge. The findings provided the factors affecting the 3D printing of food, its mechanisms, and its significance.